2017
DOI: 10.5194/amt-2017-257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrieval of tropospheric NO<sub>2</sub> columns over Berlin from high-resolution airborne observations with the spectrolite breadboard instrument

Abstract: Abstract. This paper presents the retrieval method that was developed to derive tropospheric NO 2 columns from UV/VIS spectral measurements obtained with the Spectrolite Breadboard Instrument during the AROMAPEX campaign in Berlin (April 2016). A typical DOAS retrieval approach is followed. For the calculation of air mass factors this study specifically focuses on the impact of the surface reflectance, which varies considerably from pixel to pixel over this urban region. Groundbased aerosol optical thickness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The corresponding surface reflectances, and viewing and sun geometries recorded by the AirMAP instrument are also provided in the plot, as well as the other RTM parameter settings. A strong dependence of the AMF on the surface reflectance can be observed, consistent with previous studies reported in Lawrence et al (2015), Meier et al (2017) and Tack et al (2017). In Fig.…”
Section: Amf Dependence On the Surface Reflectancesupporting
confidence: 92%
See 3 more Smart Citations
“…The corresponding surface reflectances, and viewing and sun geometries recorded by the AirMAP instrument are also provided in the plot, as well as the other RTM parameter settings. A strong dependence of the AMF on the surface reflectance can be observed, consistent with previous studies reported in Lawrence et al (2015), Meier et al (2017) and Tack et al (2017). In Fig.…”
Section: Amf Dependence On the Surface Reflectancesupporting
confidence: 92%
“…The Airborne imaging DOAS instrument for Measurements of Atmospheric Pollution (AirMAP) has been developed for the purpose of airborne trace gas measurements and pollution mapping by the Institute of Environmental Physics in Bremen (IUP-Bremen). The instrument specifications and previous campaign results have been thoroughly discussed in Schönhardt et al (2015) and Meier et al (2017). AirMAP is a pushbroom UV-Vis imager with a wide FOV of around 51.7°, resulting in a swath width of approximately the same size as the flight altitude.…”
Section: Airmapmentioning
confidence: 99%
See 2 more Smart Citations
“…NO 2 amounts over industrial regions and urban areas have been mapped at high spatial resolution by several recently developed airborne push-broom sensors (Heue et al, 2008;Popp et al, 2012;Schönhardt et al, 2015;Lawrence et al, 2015;Nowlan et al, 2016;Meier et al, 2017;Tack et al, 2017Tack et al, , 2018Vlemmix et al, 2017;Broccardo et al, 2018). Airborne remote-sensing CH 2 O measurements have previously been made from aircraft using limb-viewing geometry by airborne multi-axis differential optical absorption spectroscopy (AMAX-DOAS) (Baidar et al, 2013) and by the whisk-broom scanning technique (where the cross-track spatial dimension is provided by mechanical scanning) using the Airborne Compact Atmospheric Mapper (ACAM) (Liu et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%